In−situ sludge reduction and carbon reuse in an anoxic/oxic process coupled with hydrocyclone breakage. (15th September 2018) - Xu, Yinxiang; Fang, Yuanyuan; Wang, Zhenhua; Guo, Dan; Liu, Yi; Huang, Yuan; Fu, Pengbo; Jin, Juehui; Wei, Chenwen; Wang, Hualin; Zeng, Tao
Abstract: The long−term performance of an anoxic−oxic−hydrocyclone (AOH) process with an in−situ hydrocyclone treatment unit in the mixed liquid return line for sludge reduction and carbon reuse has been observed, in comparison with a conventional anoxic−oxic (AO) process. Three parallel side−stream systems, including one AOH25 system with a 25−mm hydrocyclone, one AOH35 system with a 35−mm hydrocyclone and one AO system, were built and fed with real wastewater for a comparative study in a wastewater treatment plant. The results demonstrate that the hydrocyclone in the AOH process was able to break macro−flocs into smaller flocs. And the desorption of the extracellular polymeric substance from return activated sludge (AS) leaded to an average increase of 62.97% and 36.36% in SCOD in the AOH25 and AOH35 system, respectively. In addition, shear forces, centrifugal forces of revolution and flocs' rotation in the hydrocyclone were proposed to be the main influence mechanism of hydrocyclone treatment on AS properties. Compared with the AO process, the SCOD concentration in the effluent of the AOH processes presented a decrease of 12.0 mg/L and the TN was reduced by 21.50% owing to the released carbon sources reuse. Moreover, the sludge production was reduced by 36.81% and 35.92% in the AOH25 and AOH35 process, respectively. By contrast, the AOH25 system was better than the AOH35 system. Graphical abstract: Image 1 Highlights: The anoxic-oxic-hydrocyclone (AOH) process fed with real wastewater was studied. In-situ hydrocyclone treatment of activated sludge enhanced carbon source release. The TN in the effluent was reduced by 21.50% due to released carbon source reuse. Denitrification efficiency improved by 35.14% during the continuous AOH operation. Sludge production in AOH process was reduced by 36.81% in comparison to AO process.